Does Firm Characteristics Affect Foreign Investors’ Transactions? The Evidence from the Vietnam Stock Market - Thao, Nguyen Thi Phuong; Thuong, Vu Thi; Hien, Nguyen Thi Tam (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
This paper aims to examine if firm characteristics had an impact on foreign investors’ decisions on buying and selling Vietnamese listed firms’ stocks between 2015 and 2019. Despite the vast majority of research in the same fields worldwide, answers to this question were not clear. Employing panel data estimation of 222 non-financial firms in the Vietnam stock market, the result of this study indicates that foreign investors have a strong preference for firms with high market capitalization, liquidity, and profitability, whereas they seem to be reluctant to invest in ones with high leverage and price to book values. However, we fail to find clear evidence of the impact of dividend yield on the number of shares bought or sold by foreign investors. Based on these results, this study proposes important policy implications to attract foreign investment in the stock market in Vietnam.